Study of motor capacities of obese and eutrophic adolescents - Calvete, Suzete dos Anjos (2010)
The aim of the study was to analyse the muscular strength and the flexibility in obese and eutrophic adolescents with 15 and 18 years of age. In order to do so, the sample was comprised of 179 adolescents: 85 obese and 94 eutrophic, of both genders. The body mass and height were measured. To classify obesity and eutrophy, the cut-off values of body mass index proposed by MUST, DALLAL and DIETZ (1991) were adopted. The evaluation of the motor capacities consisted of the following tests: handgrip, modified sit-up, modified pull-up and six measures of flexibility with the fleximeter. The main results demonstrated that the obese adolescents, when compared to the eutrophic adolescents of the same gender, presented inferior values with significant differences in the abdominal muscular endurance, upper limb muscular endurance and in the flexibility of flexion and extension trunk, knee flexion, hip flexion and abduction movements (p<=0.05). In the movement of shoulder abduction, only the girls presented difference significant, being the inferior values for the obese ones (p<=0.05). Our data suggest that obesity had a negative influence only on the motor tasks in which the body mass itself represented a natural resistance to the effort and in the range of motion of body areas in which the accumulation of body fat mass was larger.